Development of competences in the educational field: Conceptual and operational definitions - Anderson , Lucía (2022)
Currently, education relies more than ever on the developing of competence-based learning. The progress and demands of today's society poses the need of training professionals that are capable of responding to the 21st century challenges, jobs, social and personal expectations. This article is the result of a documentary analysis of different authors, and experts in the field of teaching by competences. This framework results in the formation of highly qualified, comprehensive, and research oriented individuals. Contributions are finally reflected in a competitive, vanguard, and equitable society. In conclusion, the article supports the thesis that learners’ background knowledge is at the core of competency meaningful teaching, leading to relevant, lifelong learning skills.In this sense, the education by competencies model, goes beyond academic units and contents to enhance curricular flexibility, while introducing the student into the modern informational era.